2014
DOI: 10.9790/0853-13763538
|View full text |Cite
|
Sign up to set email alerts
|

Cirrhotic Cardiomyopathy – a significant complication of Chronic Liver Disease Patients

Abstract: Key words: Cirrhotic echocardiography criteria, 6 minutes walking test MethodologyHundred patients with cirrhosis (alcoholic and non-alcoholic) were enrolled. Data collection was done by clinical history, examination, investigations. All subjects underwent Echocardiography study at rest and stress i.e. 6 minutes walking test. Observation and ResultsPrevalence of cirrhotic cardiomyopathy in my study was 91.42%. Systolic dysfunction-At the time of stress, ejection fraction was 59.78± 5.767 in cirrhotic cardiomyo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…Our study population showed predominance of male patients (82%) (Table 2) indicating that cirrhosis is more prevalent among them which was in accordance with other authors. 9,10 Most common etiology of cirrhosis was alcohol (41%), but distribution of alcoholic patients was even in the 3 MELD groups (P value: .223) (Table 2). Prevalence of CCM in our study was 48%.…”
Section: Discussionmentioning
confidence: 99%
“…Our study population showed predominance of male patients (82%) (Table 2) indicating that cirrhosis is more prevalent among them which was in accordance with other authors. 9,10 Most common etiology of cirrhosis was alcohol (41%), but distribution of alcoholic patients was even in the 3 MELD groups (P value: .223) (Table 2). Prevalence of CCM in our study was 48%.…”
Section: Discussionmentioning
confidence: 99%